2007
DOI: 10.1086/509567
|View full text |Cite
|
Sign up to set email alerts
|

Very High Energy Observations of Gamma‐Ray Burst Locations with the Whipple Telescope

Abstract: Gamma-ray burst (GRB) observations at very high energies (VHE, E > 100 GeV) can impose tight constraints on some GRB emission models. Many

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…These data are essential for the excellent temporal coverage in the VHE for this campaign. Details on the light curve presented here can be found in Pichel (2009) with the general Whipple analysis technique described in Horan et al (2007) and Acciari et al (2014). The frequencies/wavelengths covered by the campaign are radio (2.6-225 GHz), near-infrared (J, H and K), optical (B, V, g, R and I), UV (Swift/UVOT W1, W2 and M2), X-ray (0.3-195 keV), high-energy (HE) γ rays (0.1-400 GeV) and .…”
Section: The 2009 Multi-wavelength Campaignmentioning
confidence: 99%
“…These data are essential for the excellent temporal coverage in the VHE for this campaign. Details on the light curve presented here can be found in Pichel (2009) with the general Whipple analysis technique described in Horan et al (2007) and Acciari et al (2014). The frequencies/wavelengths covered by the campaign are radio (2.6-225 GHz), near-infrared (J, H and K), optical (B, V, g, R and I), UV (Swift/UVOT W1, W2 and M2), X-ray (0.3-195 keV), high-energy (HE) γ rays (0.1-400 GeV) and .…”
Section: The 2009 Multi-wavelength Campaignmentioning
confidence: 99%
“…Atkins et al 2005;Albert et al 2007;Horan et al 2007;Aharonian et al 2009), but some of the components discussed above may be eventually observed by current ground-based facilities such as MAGIC (II), HESS (II), VERITAS, CANGAROO III, or the future projects CTA, AGIS, HAWC, etc. For example, MAGIC may detect the luminous proton synchrotron emission for ǫ B /ǫ e = 100 in Figure 5 at 0.1 TeV beyond z ∼ 1, assuming E γ,iso = 10 53 erg and the latest estimates of intergalactic γγ absorption (Albert et al 2008).…”
Section: Observational Implicationsmentioning
confidence: 99%
“…Although GeV emission was detected from several GRBs by EGRET (Dingus 2003 and references therein), firm detections have yet to be achieved at TeV energies (e.g., Atkins et al 2005;Albert et al 2007;Horan et al 2007;Tam et al 2007). Theoretical expectations for the high-energy component depend strongly on the emission mechanism and the physical parameters.…”
Section: Introductionmentioning
confidence: 99%